2013
DOI: 10.1093/carcin/bgt242
|View full text |Cite
|
Sign up to set email alerts
|

BH4 domain of bcl-2 protein is required for its proangiogenic function under hypoxic condition

Abstract: Beyond its classical role as apoptosis inhibitor, bcl-2 protein promotes tumor angiogenesis and the removal of N-terminal bcl-2 homology (BH4) domain abrogates bcl-2-induced hypoxia-inducible factor 1 (HIF-1)-mediated vascular endothelial growth factor (VEGF) expression in hypoxic cancer cells. Using M14 human melanoma cell line and its derivative clones stably overexpressing bcl-2 wild-type or deleted of its BH4 domain, we found that conditioned media (CM) from cells expressing BH4-deleted bcl-2 protein showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Human umbilical endothelial cells (HUVEC; PromoCell GmbH, Heidelberg, Germany) were cultured as previously reported (Gabellini et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human umbilical endothelial cells (HUVEC; PromoCell GmbH, Heidelberg, Germany) were cultured as previously reported (Gabellini et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The negative and positive controls contained heparin alone or heparin plus VEGF (60 ng/mice; R&D Systems, Minneapolis, MN), respectively. After 5 days, the angiogenic response was evaluated by macroscopic analysis at autopsy, and by measurement of the hemoglobin (Hb) content in the pellet of matrigel as previously reported (Gabellini et al, 2013). The values were expressed as optical density (OD at 540 nm)/100 mg of matrigel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 promotes tumor angiogenesis and BH4 deletion abrogates hypoxia-inducible factor (HIF)-1-mediated vascular endothelial growth factor (VEGF) expression in hypoxic tumor cells [27]. Xenografts derived from cells expressing ΔBH4 Bcl-2 showed a reduction of metastatic potential compared with those derived from cells expressing wild-type Bcl-2 [26]. A summary of proteins including those important ones highlighted above associated with the Bcl-2 BH4 domain and their functions is provided in Table 1.…”
Section: Functions Of Bcl-2 Bh4 Domainmentioning
confidence: 99%
“…In this context, we demonstrated that removal of or mutations at the BH4 domain abrogate the ability of bcl-2 to induce Vascular Endothelial Growth Factor expression and transcriptional activity, 12 reduce the interaction between bcl-2 and Hypoxia Inducible Factor-1α proteins and the capability of exogenous bcl-2 protein to localize in the nucleus 13 and mediate inhibition of autophagy.…”
mentioning
confidence: 95%